Zonisamide add‐on therapy for focal epilepsy - Brigo, Francesco (Cochrane Database Syst Rev, 2018)
BACKGROUND: The majority of people with epilepsy have a good prognosis, and their seizures can be well controlled with the use of a single antiepileptic agent, but up to 30% develop refractory epilepsy, especially those with focal seizures. In this review, we summarised the evidence from randomised controlled trials (RCT) of zonisamide, used as an add‐on treatment for focal epilepsy uncontrolled by one or more concomitant antiepileptic drug. This is an updated version of the Cochrane review previously published in 2013. OBJECTIVES: To evaluate the efficacy and tolerability of zonisamide, when used as an add‐on treatment for people with focal epilepsy uncontrolled by one or more concomitant antiepileptic drugs. SEARCH METHODS: For this update, on 4 September 2017, we searched the Cochrane Epilepsy Group Specialised Register, Cochrane Register of Studies Online, MEDLINE Ovid, ClinicalTrials.gov, and the WHO International Clinical Trials Registry Platform ICTRP. We searched SCOPUS on 13 February 2013, but this is no longer necessary, because RCTs and quasi‐RCTs in Embase are now included in CENTRAL. In addition, we contacted Eisai Limited (makers and licensees of zonisamide) and experts in the field to seek any ongoing or unpublished studies. SELECTION CRITERIA: Randomised controlled trials, in which add‐on zonisamide was compared with placebo or another antiepileptic drug in people with focal epilepsy, uncontrolled by one or more concomitant antiepileptic drugs. DATA COLLECTION AND ANALYSIS: Two review authors independently selected trials for inclusion, extracted data, assessed for risk of bias using the Cochrane 'Risk of bias' tool, and assessed the quality of the evidence, using the GRADE approach. The primary outcome was at least a 50% reduction in total seizure frequency; the secondary outcomes were (1) tolerability; and (2) adverse effects. We used an intention‐to‐treat approach for our primary analyses. We estimated summary risk ratios (RRs) for each outcome. We displayed a summary of the estimates of effects and quality of the evidence for each outcome in a 'Summary of findings' table. MAIN RESULTS: We included eight studies (1636 participants). The overall RR with 95% confidence interval (CI) for at least a 50% reduction in seizure frequency compared to placebo for 300 mg to 500 mg/day of zonisamide was 1.90 (95% CI 1.63 to 2.22; 7 trials, 1371 participants; moderate‐quality evidence). The RR for 50% reduction in seizure frequency compared to placebo for any dose of zonisamide (100 mg to 500 mg/day) was 1.86 (95% CI 1.60 to 2.17; 7 trials, 1429 participants; moderate‐quality evidence). The number needed to treat for an additional beneficial outcome was six (95% CI 4.1 to 6.8) for this outcome. Two trials provided evidence of a dose‐response relationship for this outcome. The RR for treatment withdrawal for 300 mg to 500 mg/day of zonisamide compared to placebo was 1.59 (95% CI 1.18 to 2.13; 6 trials, 1099 participants; moderate‐quality evidence), and for 100 mg to 500 mg/day was 1.44 (95% CI 1.08 to 1.93; 6 trials, 1156 participants; moderate‐quality evidence). The number needed to treat for an additional harmful outcome was 15 (95% CI 9.3 to 36.7). The CIs of the following adverse effects indicated that they were significantly associated with zonisamide: ataxia RR 3.85 (99% CI 1.36 to 10.93; 4 trials, 734 participants; low‐quality evidence); somnolence RR 1.52 (99% CI 1.00 to 2.31; 8 trials, 1636 participants; moderate‐quality evidence); agitation RR 2.35 (99% CI 1.05 to 5.27; 4 trials, 598 participants; low‐quality evidence); and anorexia RR 2.74 (99% CI 1.64 to 4.60; 6 trials, 1181 participants; low‐quality evidence). Across the eight studies, we rated risk of bias domains at low or unclear risk of bias apart from two studies which we rated at high risk of attrition bias. Five of the eight studies were sponsored by the drug companies that produced zonisamide. AUTHORS' CONCLUSIONS: When used as an add‐on treatment in people with focal epilepsy uncontrolled by one or more concomitant antiepileptic drugs, moderate‐quality evidence found that zonisamide was more successful than placebo at reducing the frequency of seizures by at least 50%. We were unable to identify minimum effective and maximum tolerated doses. The included trials evaluated a maximum stable‐dose phase of 18 weeks, so results cannot be used to confirm longer periods of efficacy in seizure control. The results cannot be extrapolated to monotherapy or to people with other seizure types or epilepsy syndromes.